Decolonising Medieval Fennoscandia An Interdisciplinary Study of Norse-Saami Relations in the Medieval Period - Solveig Marie, Wang (Religious Minorities in the North, 2023)
The study investigates the relationship between Norse and Saami peoples in the medieval period and focuses on the multifaceted portrayal of Saami peoples in medieval texts. Through a systematic analysis of the sources, influenced by postcolonial methodologies rooted in interpretations of archaeological material, it demonstrates the many possibilities for reading and including Saami peoples in our narration of medieval Fennoscandian history.